JAHEE external evaluation: Mirza Balaj. (25th October 2022) - Balaj, M
Abstract: The general aims and evaluation blocks concerned the extent to which JAHEE achieved its objectives, and the identification of lessons learned for future health inequalities programmes. More specific aims included: Producing knowledge: to understand the outcomes of JAHEE and build knowledge on health inequalities. Influencing decision-making: to produce results that can guide the development of policies and initiatives tackling health inequalities. Accountability: to clarify responsibilities and outcomes of JAHEE. Lessons learned: to provide recommendations for future initiatives. The evaluation was grounded in five evaluation blocks: relevance, effectiveness and impact, sustainability, dissemination, and added value. The main results will be presented.